Neuropsychological Functioning of Youth Receiving Intensive Interdisciplinary Pain Treatment. (25th May 2018) - Low Kapalu, Christina M; Hall, John J; Wallace, Dustin P
Abstract: Objective: Chronic pain is associated with school difficulties; however, there is limited published evidence on the cognitive or neuropsychological functioning of youth with chronic pain. Method: When beginning intensive interdisciplinary pain treatment, 94 youth (age = 10–18) with chronic pain completed neuropsychological assessment (e.g., intelligence, academic skills, learning and recall, and attention) and clinical questionnaires (e.g., pain and physical and psychological functioning). We compared neuropsychological scores with test norms and with clinical questionnaires. Results: Youth with chronic pain had higher verbal comprehension and full scale IQ scores than expected, below-average nondominant hand dexterity, and difficulty with visual recall. Self-reported difficulties with executive functioning were associated with small-to-moderate difficulties with objectively measured attention. Performance on neuropsychological measures was generally not associated with pain, impairment, anxiety, or depression, though catastrophizing was negatively correlated with perceptual reasoning. An expected number of these youth had learning disorders (14%); however, more than expected had an autism spectrum disorder (9%) or attention deficit hyperactivity disorder (18%), and nearly a quarter demonstrated characteristics of nonverbal learning disability (22%). Conclusions: Some of these cognitive findings may be a consequence of chronic pain, and others may reflect subtle neurodevelopmental differences that may predate or be comorbid with pain. Regardless of etiology, with more than half the current sample experiencing some type of learning challenge, often undiagnosed, pediatric psychologists evaluating youth with chronic pain may wish to screen for comorbid learning difficulties.